The Political Existence of Muslim Immigrants in The United Kingdom - Minan, Jeni; Ismail, Hanim; Jamal, Mohamad Basri Bin; Danial, Dian Wahyu (Journal of Government and Civil Society, 2025)
This paper examines the political existence of British Muslim immigrants amidst the negative Western perception of Islam. The approach used is descriptive qualitative with library research. This paper concludes that the negative image constructed by the West of Islam does not eliminate the political existence of British Muslim immigrants. This is evidenced by the election of Muslim politicians from both the Labour and Conservative parties to political positions in Britain, whether as mayors, members of parliament, or ministers. However, sentiment against Muslim immigrants cannot be eliminated because terrorist acts carried out by Muslim groups that do not represent Islam have an impact on Muslims themselves, who have actually grown and developed and enjoyed the freedom to practice their religion in Britain. These acts of terrorism are often described by Muslim scholars as foolishness.Artkel ini mengkaji eksistensi politik imigran Muslim Inggris di tengah persepsi negatif Barat terhadap Islam. Pendekatan yang digunakan adalah deskriptif kualitatif dengan metode studi pustaka. Makalah ini menyimpulkan bahwa citra negatif yang dibangun oleh dunia Barat terhadap Islam tidak menghapus eksistensi politik imigran Muslim di Inggris. Hal ini dibuktikan dengan terpilihnya politisi Muslim dari Partai Buruh maupun Partai Konservatif ke berbagai jabatan politik di Inggris, baik sebagai wali kota, anggota parlemen, maupun menteri. Namun, sentimen terhadap imigran Muslim tidak dapat sepenuhnya dihilangkan karena tindakan terorisme yang dilakukan oleh kelompok-kelompok yang mengatasnamakan Islam—padahal tidak mewakili ajaran Islam—berdampak pada komunitas Muslim itu sendiri. Padahal, komunitas ini telah tumbuh dan berkembang serta menikmati kebebasan dalam menjalankan ajaran agamanya di Inggris. Tindakan terorisme tersebut sering kali digambarkan oleh para cendekiawan Muslim sebagai bentuk kebodohan.